Sub‐10 nm Polyamide Nanofiltration Membrane for Molecular Separation. Issue 15 (19th December 2019) - Hou, Junjun; Jiang, Meihuizi; He, Xiao; Liu, Pengchao; Long, Chang; Yu, Lian; Huang, Zhiwei; Huang, Jin; Li, Lianshan; Tang, Zhiyong
Abstract: To separate small molecules from the solvent with high permeability and selectivity, the membrane process is thought to be highly effective with much lower energy consumption when compared to the traditional thermal‐based separation process. To achieve high solvent permeance, a sub‐10 nm thick polyamide nanofiltration membrane was synthesized through interfacial polymerization of ethidium bromide (EtBr) and trimesoyl chloride (TMC). Thanks to the extremely low solubility of the EtBr monomer in the organic phase, the polymerization process was strictly limited at the interface of the water and hexane, leading to an ultrathin polyamide membrane with a thickness down to sub‐10 nm. When used in nanofiltration, these ultrathin membranes display ultrafast water permeation of 40 liter per square meter per hour per bar (L m −2  h −1  bar −1 ), and a high Congo red rejection rate of 93 %. This work demonstrates a new route to synthesize ultrathin polyamide membranes by the traditional interfacial polymerization. Abstract : A sub‐10 nm polyamide nanofiltration membrane was synthesized through interfacial polymerization due to the extremely low solubility of the ethidium bromide monomer in organic phase, which strictly limits the polymerization process at the interface of the water and hexane. Thanks to the ultrathin thickness, these membranes show excellent water permeance and high dye rejection.